Corn Cost-Return Budget in South Central Kansas - Dumler, Troy J.; Duncan, Stewart R. (My University, 2002)
This publication provides estimated cost and returns for forward farm planning for corn in south central Kansas.
MF2157_2002_10
Keywords: MF2157; Crops; Economics; MF